Intra-Abdominal Localisation of a Buschke-Lowenstein Tumour: Case Presentation and Review of the Literature. (18th September 2013) - Wester, N. E.; Hutten, E. M.; Krikke, C.; Pol, Robert A.
Abstract : Giant condyloma acuminatum or Buschke-Lowenstein tumour is a very rare disease which usually is located in the genital, anorectal, and perianal regions. It is regarded as a type of verrucous carcinoma occurring on anogenital mucosal surfaces where it is locally invasive but displays a benign cytology. We describe a case of a 24-year-old woman with persisting condyloma acuminata progressing to a large intra-abdominal Buschke-Lowenstein tumour. To our knowledge such an advanced stage has only been reported once before. The severity and extent of the tumour both determine the treatment and patient outcome. Treatment was impeded by cachexia, an immunosuppressive state after kidney transplantation and difficulties in establishing a reliable diagnose. Interferon treatment was started which initially led to tumour reduction but was complicated by an interferon-induced pancreatitis, pneumonia, and fasciitis necroticans resulting in death. We present a literature overview on the treatment options for a Buschke-Lowenstein tumour, with emphasis on interferon therapy, with all the advantages and disadvantages.